Bacteriophage-based nanoprobes for rapid bacteria separation. Issue 39 (28th August 2015) - Chen, Juhong; Duncan, Bradley; Wang, Ziyuan; Wang, Li-Sheng; Rotello, Vincent M.; Nugen, Sam R.
Abstract : A nanoscale bacteriophage-modified magnetic nanoprobe is developed for the low-cost and efficient separation of bacteria from liquid samples. Abstract : The lack of practical methods for bacterial separation remains a hindrance for the low-cost and successful development of rapid detection methods from complex samples. Antibody-tagged magnetic particles are commonly used to pull analytes from a liquid sample. While this method is well-established, improvements in capture efficiencies would result in an increase of the overall detection assay performance. Bacteriophages represent a low-cost and more consistent biorecognition element as compared to antibodies. We have developed nanoscale bacteriophage-tagged magnetic probes, where T7 bacteriophages were bound to magnetic nanoparticles. The nanoprobe allowed the specific recognition and attachment to E. coli cells. The phage magnetic nanprobes were directly compared to antibody-conjugated magnetic nanoprobes. The capture efficiencies of bacteriophages and antibodies on nanoparticles for the separation of E. coli K12 at varying concentrations were determined. The results indicated a similar bacteria capture efficiency between the two nanoprobes.